From Revelation to Renaissance: Arabic’s Contribution to Islamic Epistemology and Knowledge Integration - Eka Mahendra Putra; Andi Abdul Hamzah; Kamaluddin Abunawas (Journal of Innovative and Creativity, 2025)
This article investigates the historical and linguistic significance of the Arabic language within Islamic civilization, particularly focusing on its role during the Islamic Golden Age. Employing qualitative methods, including historical chronology and semiotic-linguistic analysis, the study explores how Arabic facilitated intellectual development and cultural integration across diverse regions. Findings reveal that Arabic significantly shaped Islamic epistemology through its structural precision and facilitated knowledge codification in philosophy, science, and administration. The Abbasid-era translation movements notably enabled integration of Greek, Persian, and Indian traditions, enhancing Arabic’s role as a lingua franca and intellectual medium. Arabic's linguistic flexibility allowed effective communication and synthesis of complex scientific and philosophical ideas, underpinning its role as a cultural bridge between East and West. Major centers like Baghdad’s House of Wisdom exemplify this scholarly collaboration, profoundly impacting medieval and contemporary global intellectual traditions. This study highlights Arabic’s critical contribution to epistemological developments and its ongoing cultural relevance, suggesting deeper interdisciplinary investigations into Arabic’s contemporary scholarly and educational applications.